Verificação da sensibilidade longitudinal do questionário de qualidade de vida AVVQ Brasil ao tratamento não-cirúrgico da doença venosa crônica - Leal, Flavia de Jesus [UNIFESP] (2018)
Introduction. Longitudinal sensitivity is an important property of a quality of life questionnaire that is being capable of reflecting the changes that have occurred over time in a variable, which should be investigated in the psychometric validation of an evaluation measure, such as the AVVQ-Brazil. Objective. To verify longitudinal sensitivity to the clinical changes of the Aberdeen quality of life questionnaire for varicose veins (AVVQ-Brazil) in phlebopathic subjects submitted to non-surgical treatment. Methods. Longitudinal validation study in which 112 chronic venous patients submitted to elective sclerotherapy with glucose and / or foam, Unna boot and / or dressings were evaluated for CEAP and pain visual analogue scale (VAS pain), as well as responding to the AVVQ-Brazil questionnaire and the Brazilian version of the VEINES-QOL / Sym in the pre (basal) and post-treatment moments, with an interval of 4 weeks between the assessments. Results expressed in mean, median, maximum and minimum values and standard deviation. Internal consistency of the questionnaire assessed by Cronbach's α. The differences in the scores of the scales between moments were seen by the Student's parametric t-test and the Z Wilcoxon nonparametric, and the latter also evaluated the distribution of the patients by CEAP and the moments of evaluation. Effect size, confidence interval analysis, and eta-quadrante parcial (η2p) were used to verify sensitivity to changes occurred in the scales scores. Correlation coefficients of Pearson, Spearman and η_b of Kendall were used to correlate the changes occurred in the scores of the scales themselves and between the scores of different scales. Results. Of the 112 patients, 92 (82.1%) were female. The mean age of the sample was 59.51 years ± 14.03, posture in prolonged orthostatism (49.1%), with at least incomplete elementary school (22.3%), complete 2nd grade (22.3%) or complete 3nd grade (25%) and severity of the disease in classes C2 (28.6%) and C6 (32.1%) of clinical CEAP. It is worth noting the general decrease in values of averages between the moments for all scales, except for the Varicosity Extension domain of the AVVQ-Brazil and the VEINES-QOL/SYM after 4 weeks. Cronbach's α indicated, in general, moderate to high reliability of AVVQ-Brazil. The effect size indicated a small sensitivity to the AVVQ-Brazil and its domains and VAS pain, in addition to small to moderate sensitivity to the VEINES-QOL/SYM. The partial η 2 also showed, in general, small to large sensitivity of the scales. It was observed that most of the patients improved or maintained the same post-treatment CEAP clinical class, with a significant statistical difference. The correlation coefficients presented moderate to excellent correlations between the changes of the scales over time, with statistically significant differences. Conclusion. AVVQ-Brazil was sensitive to post-treatment small clinical changes in individuals with CVD, being an important measure of the QoL and severity of the disease in Brazil.